2013
DOI: 10.15835/nbha4118344
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Volatile Aroma Compounds of Morchella by Headspace Gas Chromatography Mass Spectrometry (HS-GC/MS)

Abstract: This study was conducted at the Horticulture Department of Çukurova University, Adana, Turkey, in 2010 to determine the volatile aroma compounds of Morchella mushroom. Fresh samples of Morchella esculenta (Sample 1) and Morchella elata (Sample 2) were collected from Çanakkale (Sample 1) and Mersin (Sample 2) provinces in Turkey in the spring of 2010. Volatile aroma compounds were analyzed by headspace gas chromatography mass spectrometry (HS-GC/MS). A total of 31 aroma compounds were identified in the 2 analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
(8 reference statements)
0
11
1
2
Order By: Relevance
“…Nonanal was the most abundant aldehyde, with 7.2% of the area of total volatiles (33% of aldehydes), whereas Z ‐9,17‐octadecadienal, benzeneacetaldehyde, E , E ‐2,4‐heptadienal, benzaldehyde, hexanal and 3‐methylbutanal ranged between 1.3 and 2.7%, and peak areas of heptanal, 2‐heptenal, octanal, E , E ‐2,4‐nonadienal, 2‐decenal ( Z ‐ and E ‐ isomers co‐eluted), benzeneacetaldehyde‐α‐ethylidene and E , E ‐2,4‐decadienal were 0.7% to trace amounts. Only two aldehydes were identified in a previous report on morel aroma: decanal and nonanal . Of these, only nonanal could be identified in our samples (Table ).…”
Section: Resultsmentioning
confidence: 47%
See 3 more Smart Citations
“…Nonanal was the most abundant aldehyde, with 7.2% of the area of total volatiles (33% of aldehydes), whereas Z ‐9,17‐octadecadienal, benzeneacetaldehyde, E , E ‐2,4‐heptadienal, benzaldehyde, hexanal and 3‐methylbutanal ranged between 1.3 and 2.7%, and peak areas of heptanal, 2‐heptenal, octanal, E , E ‐2,4‐nonadienal, 2‐decenal ( Z ‐ and E ‐ isomers co‐eluted), benzeneacetaldehyde‐α‐ethylidene and E , E ‐2,4‐decadienal were 0.7% to trace amounts. Only two aldehydes were identified in a previous report on morel aroma: decanal and nonanal . Of these, only nonanal could be identified in our samples (Table ).…”
Section: Resultsmentioning
confidence: 47%
“…Identified methyl esters for Morchella included nine C6–C16 aliphatic esters, as well as one aromatic ester, methyl benzoate (Table ). No methyl esters have ever been recorded in morels, although these compounds have been identified as important to the aroma of other mushrooms …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gas chromatography–mass spectrometry analysis demonstrated that the main lipid components in the skin secretion of Bokermannohyla alvarengai are saturated fatty acids. Nine of the eleven main peaks revealed in the analysis seem to be components of the skin secretion; the remaining two, i.e., Peak 3 (phthalic acid, decyl methyl ester) and Peak 8 [1,2‐benzenedicarboxylic acid, bis(2‐methylpropyl) ester], are common components of plants (Taskin, ; Vimalavady and Kadavul, ) and are probably contaminants resulting from the preparation of the samples. One of the most abundant lipid molecules found in the skin secretion of B. alvarengai is sphenol, 2,4‐bis(1,1‐dimethyl)‐ (Peak 2), which is a chemical intermediate for the synthesis of UV stabilizers or antioxidants.…”
Section: Discussionmentioning
confidence: 99%